Comprehensive Cybersecurity Framework for Digital Governance: Threat Assessment, Risk Mitigation, and Regulatory Compliance in Indonesia - Wildan Maulana Assani Mualim; Fitri Yul Dewi Marta; Ira Meiyenti (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation of government administration brings significant benefits in improving public service efficiency and citizen access to information. However, digitalization also opens opportunities for increasingly complex and organized cyber threats. This journal explores a comprehensive cybersecurity framework for digital governance through an extensive literature review that includes threat assessment, risk mitigation strategies, and regulatory compliance analysis. This research analyzes international frameworks (NIST CSF 2.0, ISO/IEC 27001:2022, COBIT 2019), Indonesian national standards (Law No. 1 of 2024 on Information and Electronic Transactions, SPBE, BSSN), and best practices in incident response and Zero Trust Architecture. Results demonstrate that government cybersecurity requires a holistic approach integrating technical aspects, policy, human resources, and governance. This journal recommends implementing a comprehensive cybersecurity framework, enhancing human capital capacity, adopting cutting-edge technology, and fostering inter-institutional coordination to build sustainable cybersecurity resilience for government entities.